(2575) Proposal to conserve the name Protocupressinoxylon with a conserved type against Protobrachyoxylon (fossil plants) - Bodnar, Josefina (2017)
It is proposed that conservation of Protocupressinoxylon be with a conserved type in view of the fact that the original specimens of the species names included in the protologue are lost or do not match the diagnosis. The conserved type proposed is Protocupressinoxylon malayense Roggeveen (in Proc. Sect. Sci. Kon. Akad. Wetensch., Amsterdam 35: 580–584. 1932) which is based on well-described material and fits the generic diagnosis.